Evaluation of new composite rigid joint under cyclic loading and its effect on one-floor composite frame - Azadeh Haghighat; Neamat Allah Heydarian; Mohammad Kazem Sharbatdar (Journal of Structural and Construction Engineering, 2017)
In order to improve the performance of structure against lateral and gravity loads, new systems known as composite systems consisting of the reinforced concrete columns and steel beams (RCS) can be used and thereby the advantages of concrete beside steel are acquired. RCS joints can be implemented as either through-beam-type joint or through-column-type joint. In this paper, a concrete joint as standard reference joint and a proposed composite joint through-column‎ with new details were built and tested under cyclic loading. Then, using numerical analysis by finite element method, the behavior of composite joint under cyclic loading has been studied and the behavior and performance of proposed composite joint has been studied by comparing the results with that of concrete joint. The results showed that the joint composition in this way resulted in decreasing of the compressive and tensile damages of concrete and increasing in loading capacity, ductility, stiffness and energy absorption. General results of application of composite joint at the one floor-one span composite frame indicating that lateral loading capacity of frame was increased and the performance of frame was improved.